Application of EU Geographical Indications for the Protection of Smoked Dry-Cured Ham—Impact on Quality Parameters - Ana Gugić Ratković; Martina Turk; Helga Medić; Danijel Karolyi; Nives Marušić Radovčić (Foods)
This study compares Dalmatinski pršut, an EU Protected Geographical Indication (PGI)-labelled smoked dry-cured ham from the Dalmatia region in Croatia, with non-PGI hams from the same area, focusing on the impact of PGI certification on the product quality. The investigation is prompted by the increasing presence of dry-cured hams lacking the PGI label on the market, aspiring to compete with esteemed high-value PGI products. Samples of 28 smoked dry-cured hams (12 PGI and 16 non-PGI) were analysed for chemical properties, fatty acid composition, volatile compounds, PAH content and sensory characteristics. The results showed that PGI and non-PGI hams differ in their chemical and physical properties, with non-PGI hams having a lower water content and a higher salt content, which was also confirmed by the saltier taste in the sensory evaluation. PGI hams had a lower b* colour value, and, while the differences in texture were minimal, non-PGI hams had slightly more monounsaturated fatty acids. The aroma analysis revealed that PGI hams contained more aldehydes and alcohols, while non-PGI hams had a higher content of phenolic compounds and aromatic hydrocarbons, probably due to differences in smoking practices. PAH levels, however, were within the EU limits, indicating controlled smoking of both type of hams. Overall, these results show that the quality of smoked dry-cured ham can be distinguished by the PGI designation. The study illustrates how the traditional production methods prescribed by the PGI production protocols shape the sensory and chemical profiles of Dalmatinski pršut, with the PGI certification playing a crucial role in maintaining product quality and certifying its typicality, to distinguish it from non-PGI products.